Pengembangan Media Pembelajaran Fisika Berbantuan Scratch pada Topik Konversi Suhu untuk Meningkatkan Hasil Belajar Siswa - Salma, Yessy Umi; Perdana, Riki (Universitas Garut, 2024)
The low learning outcomes of students in physics, particularly on the topic of temperature conversion, remain a prevalent issue in Indonesia. This study aims to develop Scratch-assisted learning media to improve student learning outcomes on this topic. The research employed the 4D model (Define, Design, Development, Disseminate). Validation was conducted by three validators, consisting of prospective physics teachers, using questionnaires that assessed aspects of design, accessibility, and language. The validation results yielded an average score of 3.6 for design, 3.9 for accessibility, and 3.7 for language, categorized as suitable to highly suitable. The learning media incorporates interactive features, including instructional content, simulations, and evaluations, developed using Scratch to enhance students’ motivation and understanding of temperature conversion concepts. The findings demonstrate that the developed learning media is effective in improving student learning outcomes.